KEBIJAKAN PENEGAKAN HUKUM TERHADAP PELAKUTERORISME DI INDONESIA PADA MASA REFORMASI, CAPAIAN DAN TANTANGAN - Sri Yunanto (Universitas Muhammadiyah Jakarta, 2017)
This research seeks to understand the law enforment policy made by the government of Indonesia on the counter terrorism(CT) particularly during the reformasi era. The law enforcement consists of detention, interrogation, investigation, tribunal and imprisonment.This research uses qualitative approach with the collection of secondary data in terms of document analysis and the employment of policy making and law enforcement as theoretical framework. This paper come to the conclusion that,in fact, the government of Indonesia has enacted legal frame works in terms of laws, and other ministe- rial decrees which serve as the foundation in the law enforcement of counter terrorism.International community has praised Indonesia for its success in the detention, interrogation, investigation and tribunal measures. However, the implementation of law enforment in the CT still poses number of problems and challenges, comprising from legal foundation and other law enforcement measures. The Indonesian parliament in now undergoing the revision of the law hs been perceived as weak for CT strategies. Polri still conduct number of extra judicial killings and are perceived as jeopardizing Muslims.The imprisonment fail to impose the dera- dicalization of the terrorists, leading to their return to terrorist network and involvement in supporting ISIS.Keywords: policy, law enformnet, terorism, goal, challenge